Avaliação da resposta de macrófagos inflamatórios frente aos cimentos biocerâmico. - Layara Cristine Tomaz Tavares (2019)
The properties and compositions of endodontic sealers may influence the periradicular inflammatory reactions and compromise the success of endodontic treatment. Macrophages are present in the periapical inflammatory infiltrate, being involved in the microbial clearance in this region. This study evaluated the cell viability, adhesion, phagocytosis of S. boulardii, production of reactive oxigen species (ROS) and nitrite oxide (NO) and cytokines (TNF and TGF-β) by murine peritoneal macrophages of pro-inflammatory (M1) and anti-inflammatory (M2) profiles obtained from C57BL / 6 and BALB / c mice, respectively. Macrophages were obtained and the cell suspension was placed in contact with capillaries containing or not the sealers Endosequence BC Sealer (BC), Sealer PLus BC (MK), Bio-c Sealer (Ang) e MTA. Cell viability was measured by the methods of tripan blue exclusion and by MTT at times 24, 48 and 72 hours. In the first assay, similar cell viability was found between the bioceramic and the MTA in the tested times; However, there was a significant difference in 72h between BC and control (empty capillary); For the MTT there was a difference with the control between: Ang (24h), BC e MK (48h) para M1; para M2, MK (24h), Ang (48h) e BC, Ang, MTA (72h) (p<0,05). n the adherence and phagocytosis assays there was no significant difference for the materials tested in both macrophage subtypes. Regarding the production of ROS, there was a greater expression for M1 compared to M2. In the absence of Zymosan there was no significant production between the sealers for both macrophages. In the presence of Zimosan A, the MK cement presented higher production than the groups treated with Ang and MTA, and control (p <0.05) for M1 macrophages. n the NO detection assay, in the presence of the stimulus, all the sealers tested showed significant differences with the control, for the M1 macrophage. In the TNF there was only difference for M1, with a higher production by the Endosequence BC even without stimulus, when stimulated with IFN-γ, BC showed higher production than the treated groups MK and Ang; and all groups showed differences in relation to control. The TGF-β dosage did not present difference for the groups treated in the presence or absence of the stimulus. It was concluded that the calcium silicate composition, similar to that of MTA, allowed the bioceramics to not interfere in the macrophages responses of both tested strains.